2018
DOI: 10.1038/s41598-018-29744-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulation accounts for the neuroprotective properties of anthocyanins

Abstract: High-fat (HF) diets are thought to disrupt the profile of the gut microbiota in a manner that may contribute to the neuroinflammation and neurobehavioral changes observed in obesity. Accordingly, we hypothesize that by preventing HF-diet induced dysbiosis it is possible to prevent neuroinflammation and the consequent neurological disorders. Anthocyanins are flavonoids found in berries that exhibit anti-neuroinflammatory properties in the context of obesity. Here, we demonstrate that the blackberry anthocyanin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…Improvements in life expectancy of the majority of citizens worldwide has led the World Health Organization (WHO) to predict that by 2040, neurodegenerative diseases will surpass cancer as the second reason of death after cardiovascular diseases in such aged populations . As per a 2017 report, neurological diseases cost the United States of America about $800 billion annually and this number is expected to increase even further over the coming years as the percentage of aged citizens increases …”
Section: Introductionmentioning
confidence: 99%
“…Improvements in life expectancy of the majority of citizens worldwide has led the World Health Organization (WHO) to predict that by 2040, neurodegenerative diseases will surpass cancer as the second reason of death after cardiovascular diseases in such aged populations . As per a 2017 report, neurological diseases cost the United States of America about $800 billion annually and this number is expected to increase even further over the coming years as the percentage of aged citizens increases …”
Section: Introductionmentioning
confidence: 99%
“…Also, in a recent study, blackberry anthocyanin-rich extract was found to modulate gut-microbiota composition. Blackberry extract increased Pseudoflavonifractor when the animals were fed with the control (low fat) diet and increased Oscillobacter independently of the diet fat content [ 212 ].…”
Section: Why Anthocyanins?mentioning
confidence: 99%
“…Since gut microbiome seems to be a critical element in the communication between the gastrointestinal system and CNS, the ability of anthocyanins to modulate microbiota–gut–brain axis needs to be further scrutinized. Several studies have already unveiled the polyphenols effect on microbiota–gut–brain connection in the context of different neurological diseases [ 58 , 173 , 174 , 185 , 186 , 187 , 188 ]. Ho et al showed the impact of the diversity of gut bacteria on the synthesis of flavonoid metabolites, which may affect the alpha-synuclein misfolding, a crucial process in PD onset, and the development of motor dysfunction in a Drosophila model of α-synucleinopathy [ 185 ].…”
Section: Gut Microbiota Impact On Anti-neuroinflammatory Activity mentioning
confidence: 99%
“…Also, 3-hydroxycinnamic acid derived from successive anthocyanin metabolic events has relevant anti-depressive effect, eventually through anti-inflammatory mechanisms [ 190 ]. Importantly, a blackberry anthocyanin-rich extract attenuates the neurologic complications of obesity through the modulation of the gut microbiota composition, with the consequent impact on tryptophan metabolism and on the release of kyanurenic acid, a neuroprotective metabolite [ 188 ]. These results suggest that dietary manipulation of the gut microbial environment, via anthocyanins administration, could delay or restrict the progression of several CNS disorders.…”
Section: Gut Microbiota Impact On Anti-neuroinflammatory Activity mentioning
confidence: 99%